Evaluación de la educación financiera en microempresas del mercado Belén, Loreto; una encuesta entre propietarios y contadores, periodo 2024 - Perez Silva, Eva (2024)
The objective of this study, "Evaluation of Education and Financial Management in Microenterprises in the Belén Market, Loreto: A Survey among Owners and Accountants, 2024", was to determine the level of financial education and its impact on the financial management of microenterprises in the Belén market, Loreto. It was decided to carry out a quantitative research with a non-experimental design and the study population consisted of 50 micro-business owners and accountants. A structured questionnaire was administered to the participants to assess their knowledge and practices in financial education and management. Through analysis of the results, it was found that the majority of respondents knew quite a bit about finances, although there were some areas that needed improvement. This study establishes a solid foundation for the implementation of financial training programs aimed at improving the sustainability and strategic decision making of microenterprises in the region. The conclusions suggest that increasing financial education can have a significant positive impact on business management, promoting more effective financial practices and contributing to the economic growth of the Belén, Loreto market.